Improving Surface Finish Quality of Plastic Molds via VSM and DMAIC Integration - Kholil, Muhammad; Hidayat, Syarif; Firdaus, Alfa (Journal of Information System, Technology and Engineering, 2025)
The rapid growth of manufacturing demands continuous process improvement. This study examines a plastic manufacturing company’s Mouldshop, which has not met performance targets an average lead time of 52 days (target 50 days) and a 75% success rate (target 93%) and struggles to achieve the desired surface finish quality of plastic molds. An integrated Value Stream Mapping (VSM) and Six Sigma DMAIC approach is applied to visualize end-to-end process flows (VA/NNVA/NVA), quantify performance gaps, analyze root causes (Fishbone with the 4M Man, Machine, Material, Method), and design improvements. VSM reveals three dominant wastes defects, inappropriate processing, and waiting linked to six critical failure causes spanning operator capability and discipline; overloaded schedules, equipment failures, machining errors, temperature control, and precision instability; material selection and procurement delays; and shortcomings in work- instruction compliance, machining parameters, drawing completeness, and standardized process flow. Using 5W+1H within DMAIC, the study proposes: standardized machining instructions and setup times; preventive- maintenance schedules and checklists; incoming verification with PIC accountability; structured training; mold quality checklists; weekly 5S/5R audits; and Future State Mapping to reduce NNVA/NVA. The integrated DMAIC–VSM roadmap is expected to shorten lead time, raise the value-added ratio, and improve surface finish quality, offering a transferable blueprint for similar manufacturing operations.